A new population of terrestrial gamma‐ray flashes in the RHESSI data. Issue 24 (23rd December 2015) - Østgaard, N.; Albrecthsen, K. H.; Gjesteland, T.; Collier, A.
Abstract: Terrestrial gamma‐ray flashes (TGFs) are the most energetic photon phenomenon occurring naturally on Earth. An outstanding question is as follows: Are these flashes just a rare exotic phenomenon or are they an intrinsic part of lightning discharges and therefore occurring more frequently than previously thought? All measurements of TGFs so far have been limited by the dynamic range and sensitivity of spaceborne instruments. In this paper we show that there is a new population of weak TGFs that has not been identified by search algorithms. We use the World Wide Lightning Location Network (WWLLN) to identify lightning that occurred in 2006 and 2012 within the 800 km field of view of Reuven Ramaty High Energy Solar Spectroscopic Imager (RHESSI). By superposing 740, 210 100 ms RHESSI data intervals, centered at the time of the WWLLN detected lightning, we identify at least 141 and probably as many as 191 weak TGFs that were not part of the second RHESSI data catalogue. This supports the suggestion that the global TGF production rate is larger than previously reported. Key Points: A new population of weak TGFs TGFs might be a common phenomenon TGFs may have an important effect on atmosphere